2022
DOI: 10.1093/ehjopen/oeac070
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and discontinuation of statin treatment in Norway: potential for optimizing management of lipid lowering drugs

Abstract: Aims In clinical practice many patients do not reach the recommended treatment targets for LDL-cholesterol levels. We aimed to examine treatment patterns and adherence for patients on lipid lowering drugs in Norway to inform future strategies to improve therapies. Methods and results We obtained information on all dispensed statins, ezetimibe and PCSK9 inhibitors 2010-2019 from the Norwegian Prescription Database. Treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In 2021, 740,755 Danes were treated with a statin, corresponding to about 13% of the population [ 4 ]. These numbers are comparable to other Nordic countries like Norway [ 5 ], but higher than other northern European countries like France and the UK where 8–10% of the population take statins [ 6 , 7 ]. More than half of the statin-treated individuals in Western countries are in primary prevention and have no other major risk factors for cardiovascular disease [ 6 , 8 – 10 ].…”
Section: Introductionmentioning
confidence: 54%
“…In 2021, 740,755 Danes were treated with a statin, corresponding to about 13% of the population [ 4 ]. These numbers are comparable to other Nordic countries like Norway [ 5 ], but higher than other northern European countries like France and the UK where 8–10% of the population take statins [ 6 , 7 ]. More than half of the statin-treated individuals in Western countries are in primary prevention and have no other major risk factors for cardiovascular disease [ 6 , 8 – 10 ].…”
Section: Introductionmentioning
confidence: 54%
“…22 To assess the role of cumulative duration and dose of treatment, for each statin claim, we extracted information on date of purchase, number of tablets delivered, and dose of each tablet. Under the assumption of one tablet per day, [26][27][28] we defined the theoretical duration of use (equal to the number of tablets), the theoretical end date, and the daily dose (equal to the dose of tablet). 29 For each claim, the duration of use is the absolute difference between the date of purchase and the minimum of the theoretical end date and date of the next purchase; the total dose of a given claim is obtained by multiplying the duration by the daily dose.…”
Section: Statin Usementioning
confidence: 99%
“…4,7,8 Notwithstanding the radical change in the natural history of atherosclerotic disease promoted by statins, their long-term adherence all across the globe, as well as the compliance to LDLc goals set by various guidelines, seems way too far from ideal, which in turn, frustrates much of the expectations toward their benefits. 7,[9][10][11][12][13][14] Although Turkey has the highest prevalence of premature coronary artery disease among European countries, 15 rates of statin discontinuation continuously mount along a period of 6 months past the first prescription, and only 18% of patients in secondary prevention achieve LDLc goals <70 mg/dL: Surprising data, given the countrywide reimbursement of statins by the Turkish health system. Reasons for the low adherence and high discontinuation rate may vary among countries or regions in the same country, and the most commonly reported causes are fear of side effects by patients, coupled with low awareness of benefits, dissemination of negative or fake news, and therapeutic inertia.Worthy of mention is the inertia to associate ezetimibe as an add-on to statins when goals are not achieved: Despite its proven value to further reduce LDLc levels and cardiovascular outcomes, 6,16 data from registries have shown that its addition to statins in patients with ASCVD remains very low 9,13,17,18 and does not progress during a 2-year follow-up.…”
mentioning
confidence: 99%
“…7,[9][10][11][12][13][14] Although Turkey has the highest prevalence of premature coronary artery disease among European countries, 15 rates of statin discontinuation continuously mount along a period of 6 months past the first prescription, and only 18% of patients in secondary prevention achieve LDLc goals <70 mg/dL: Surprising data, given the countrywide reimbursement of statins by the Turkish health system. Reasons for the low adherence and high discontinuation rate may vary among countries or regions in the same country, and the most commonly reported causes are fear of side effects by patients, coupled with low awareness of benefits, dissemination of negative or fake news, and therapeutic inertia.Worthy of mention is the inertia to associate ezetimibe as an add-on to statins when goals are not achieved: Despite its proven value to further reduce LDLc levels and cardiovascular outcomes, 6,16 data from registries have shown that its addition to statins in patients with ASCVD remains very low 9,13,17,18 and does not progress during a 2-year follow-up. 19 PCSK9 inhibitors (PCSK9i) are the most efficacious non-statin LDLc-lowering agents 20 and were proven capable of reducing cardiovascular outcomes when added to maximally tolerated statin doses (MTD) in very high-risk patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation